2019
DOI: 10.15406/ppij.2019.07.00230
|View full text |Cite
|
Sign up to set email alerts
|

Yield, chemical composition and antibacterial activity of Ruta chalepensis L. essential oil growing spontaneously in Algeria

Abstract: As part of the development of Algerian natural products, mainly of plant origin, we are interested in the study of the essential oil of Ruta chalepensis L. collected from Souk ahras (North-east of Algeria) obtained by hydro-distillation. Characterization of these species was made by determining yield and chemical composition. The essential oil yield of the dried plant obtained was 0.65 % (v/w). The identification of the chemical composition of the essential oil from aerial parts was carried out thanks to gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…At 15-day, the oil content was 0.3044% and 0.287% for shade and sun, respectively. The value of essential oil content in this study was found within the range of research findings reported by [10,[29][30][31]. The specific gravity of rue essential oil was 0.860 at 0-day and 15day shade dry, 0.853 and 0.863 for 5-day and 10-day shade dry.…”
Section: Effect Of Drying On Essential Oil Compositionsupporting
confidence: 88%
“…At 15-day, the oil content was 0.3044% and 0.287% for shade and sun, respectively. The value of essential oil content in this study was found within the range of research findings reported by [10,[29][30][31]. The specific gravity of rue essential oil was 0.860 at 0-day and 15day shade dry, 0.853 and 0.863 for 5-day and 10-day shade dry.…”
Section: Effect Of Drying On Essential Oil Compositionsupporting
confidence: 88%
“…Twenty-eight (28) components were reported with the main component being 2-Tridecanone (38.88%), 2-Nonanone (29.56%), 2-Acetoxytridecane (18.58%), 2-Pentadecanol acetate (3.42%), 2-Decanone (1.67%), and 2-Dodecanone (1.25%), while other components were detected in trace amounts of less than 1% each, and the components with lowest concentrations were Gamma-Terpinen (0.02%) and o-Cymene (0.01%). Literature surveys showed great variability which could be due to factors such as geographical location, season and environmental factors, and the method of extraction (Boughendjioua, 2019). The presence of 2-Undecanone as a dominant component in R. chalepensis leaf oil extract was also reported in Ethiopia ( 18.58%) which are detected in this study, were not identified in previous studies.…”
Section: Chemical Compositioncontrasting
confidence: 55%
“…Cichorium pumilum, which is widely used as a traditional medicinal herb, showed antibacterial activity in vitro with agar disc diffusion and agar well diffusion methods against 10 different bacterial species [44]. The antimicrobial activity of Ruta chalepensis L. was tested against four pathogenic bacteria-Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa-and the findings indicate possible applications for the treatment of various infectious and noninfectious diseases [45]. The antibacterial effects of essential oil of Chrysanthemum coronarium demonstrated pronounced activity against gram-positive strains of bacteria: Bacillus subtilis (19 mm), Staphylococcus aureus (20 mm), Staphylococcus epidermidis (18 mm), Escherichia coli (9 mm), and Pseudomonas aeruginosa (12 mm), which were assessed by measuring the zone of inhibition [46].…”
Section: Resultsmentioning
confidence: 99%